A Precarious Game : The Illusion of Dream Jobs in the Video Game Industry - Bulut, Ergin (Book collections on Project MUSE., 2020)
"This book reveals the unequal politics of game development as a dream job, which only privileged subjects can enjoy, while many others have to face significant social and individual costs"--